2005
DOI: 10.1007/s00339-004-3014-2
|View full text |Cite
|
Sign up to set email alerts
|

Magneto-transport characterization of Dy123 monodomain superconductors

Abstract: The following report considers textured materials of the DyBa 2 Cu 3 O 7 type seeded with a Nd123 seed as initiator. They are grown with an excess 20% Dy211 phase on a Dy 2 O 3 substrate. We report chemical characterizations, electrical resistivity, thermoelectric power and thermal conductivity over a broad temperature range as a function of an applied magnetic field up to 6 T. We show that specific features appear on the magneto thermal transport properties different in these materials from those found in sin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 34 publications
1
4
0
Order By: Relevance
“…The modeled data are shown to agree nicely with the experiment [ figure 6(a)]. Note that the temperature difference is related directly to the thermal conductivity κ of melt-textured YBCO, for which experimental data available in the literature span a relatively large range, from ~ 0.7 W/m K to ~ 20 W/m K and is anisotropic [55][56][57][58][59]. In the present case, we take anisotropy into account and assume κ(||ab) = 11 W/m K and κ(||c) = 3 W/m K. The results of the model reproduce qualitatively the behaviour shown in the experiment: (i) an initial increase of the sample temperature nearing the vicinity of the sample corner (r = a, z = b), and (ii) a very small temperature gradient across the sample surface, although the amplitude of the applied AC field (34 mT) is smaller than the full-penetration field at 77 K (~ 124 mT).…”
Section: Temperature Distribution During Self-heating -Experiments Andsupporting
confidence: 70%
See 1 more Smart Citation
“…The modeled data are shown to agree nicely with the experiment [ figure 6(a)]. Note that the temperature difference is related directly to the thermal conductivity κ of melt-textured YBCO, for which experimental data available in the literature span a relatively large range, from ~ 0.7 W/m K to ~ 20 W/m K and is anisotropic [55][56][57][58][59]. In the present case, we take anisotropy into account and assume κ(||ab) = 11 W/m K and κ(||c) = 3 W/m K. The results of the model reproduce qualitatively the behaviour shown in the experiment: (i) an initial increase of the sample temperature nearing the vicinity of the sample corner (r = a, z = b), and (ii) a very small temperature gradient across the sample surface, although the amplitude of the applied AC field (34 mT) is smaller than the full-penetration field at 77 K (~ 124 mT).…”
Section: Temperature Distribution During Self-heating -Experiments Andsupporting
confidence: 70%
“…The modelled data are shown to agree nicely with the experiment (figure 6(a)). Note that the temperature difference is related directly to the thermal conductivity κ of melt-textured YBCO, for which the experimental data available in the literature span a relatively large range, from ∼0.7 W m −1 K −1 to ∼20 W m −1 K −1 and are anisotropic [55][56][57][58][59]. In the present case, we take anisotropy into account and assume κ ab = 11 W m −1 K −1 and κ c = 3 W m −1 K −1 .…”
Section: Temperature Distribution During Self-heating-experiments And...mentioning
confidence: 99%
“…In addition, the temperature dependence of the thermal conductivity of small bar-shaped samples was measured using a home-made experimental set-up inserted in a Quantum Design Physical Property Measurement System (PPMS) [20], [21]. Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Pekala et al [6] have reported Z value of about 2×10 -5 per K for textured samples of DyBa2Cu3O7-δ. Gonzalez et al [7] have investigated Z parameter for EuBa2Cu3O7-δ and have demonstrated that Z strongly depends on the oxygen content (7-δ).…”
Section: Introductionmentioning
confidence: 98%